Repatriation of disused sealed sources from Peru to the United States - Mallaupoma, Mario (2013)
Disused sealed radioactive sources are piled in Peru due to the peaceful use of them in medicine, industry and research for a wide range of applications. The sources may contain a broad spectrum of radionuclides, exhibiting a wide range of activity levels and radioactive half-lives. At the end of their useful lives they are defined as ‘spent’ or ‘disused’. However, the residual level of radioactivity in some sources can remain high, representing a significant radiological hazard. At this point, a decision must be made on how to properly manage the end-of-life cycle of the sources that are now disused. This paper describes technical actions developed by the specialized technical teams of IPEN and the Los Alamos National Laboratory for the repatriation of disused sources from Peru to the United States.